Advances in power generation from ammonia via electrocatalytic oxidation in direct ammonia fuel cells - Shi, H.; Tang, Jiayi; Yu, Wenqing; Tadé, Moses O.; Shao, Zongping (2024)
To achieve the global carbon neutrality goal proposed by the United Nations, seeking alternative affordable energy sources and efficient energy conversion ways has become extensive concerns. The varied applications of hydrogen energy are greatly valued for the past decades, as it releases less greenhouse gas emissions compared to traditional fossil fuels. However, large-scale hydrogen utilization is primarily limited by its storage and long-distance transportation challenges. In recent years, ammonia has been considered as an ideal alternative to hydrogen because as a good carbon-free energy carrier it shows high hydrogen content, high energy density, and easy storage and transportation. In this case, direct ammonia fuel cells (DAFCs) have received considerable attention. Ammonia oxidation reaction (AOR) over the anode exhibits a complex mechanism and slower kinetics under the lower operation temperatures compared to the hydrogen oxidation reaction (HOR) in the fuel cells. Hence, this review provides an in-time summary of the recent understanding of electrochemical AOR mechanisms and the progress in electrocatalysts design for various types of DAFCs operating from room to elevated operation temperatures. Additionally, the performance optimization of DAFCs and the existing challenges for achieving high AOR activity and selectivity in practical fuel cells are thoroughly discussed.